Study, simulation and detection of glucose concentrations through a biochip based on two-dimensional photonic crystals - Bella, Mourad; Ghoumazi, Mehdi; Slimani, Ghania; Benatia, Djamel (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
A biochip is made from a two-dimensional photonic crystal waveguide and a rhombus shape that acts as a resonator. This biochip is a sensor that can detect different concentrations of glucose with amounts of 10, 20 and 60% in water. Here, we studied and simulated the concentrations of glucose, which have a refractive index n of 1.3477, 1.3635 and 1.4394, respectively. To identify these quantities, we have proposed a square lattice structure formed by silicon rods with a n = 3.46. With the help of these dielectric rods immersed in the air, it was possible to analyze the detection characteristics. Our results are examined according to COMSOL software by using the PWE method and the finite element method in order to have the PBG and which helped us to create the structure and extract the propagation at resonance, the field norm, the total energy density (TED), the power flow norm (PFN), the transmission and the sensitivity. The concentrations of glucose in water answered yes to the variations for each of the E-field, the TED, the PFN and the sensitivity. These variations are due to the radius r and refractive index n of each concentration used. This structure can help with diabetes self-monitoring.
Optica Applicata, Vol. 53, 2023, nr 4, s. 547-562
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; photonic crystals; pwe; biochip; glucose; diabetes